Global developments and their implications for The international competitiveness of the industry in Iraq - nadhir, asraa muhamad; Rashid Al-Ani, Thaer Mahmoud (Journal of Economics and Administrative Sciences, 2020)
During the last quarter of the twentieth century , the global economy witnessed transformation in various commercial , technological and financial fields that changed its structure and produced a new situation that is mainly represented in the increasing movement of foreign capital and the rapid expansion of international production and trade in addition to the tremendous technological development and technology transfer, which led countries to Being obsessed with competing at the global level and seeking to enter international markets and improve their competitiveness. It was agreed that these factors are among the manifestations of adopted the slogan of economic and commercial openness for the sake of a global market that achieves gains and growth for all . The industrial sector is considered one of the most vulnerable sectors to the effects of changes in the international economic environment , in a way that makes the local industry in Iraq become more fragile with the passage of time , as it experiences sharp competition with global institution that have come to control the world , and this competition does not affect the institution of developing countries targeting local markets as well . this is in the environment of markets and competition , and from here it has become imperative to respond to these challenges by working to develop its competitiveness to ensure its continuity and survival which is controlled by a set of determinants whose nature differs between price , non- price organizational , facilitation technical …etc. As for the industrial sector in Iraq under the current stage , it inherited an industrial reality characterized by backwardness and shackled by many problems and obstacles that limit its activity and its ability to work in light of the new economic policy characterized by freedom of trade and the adoption of market mechanisms and economic standards in allocating resources According, we will review the most important international industrial and technological. within the global competitiveness indicators.